Innovation of Islamic Religious Education Learning Methods - Nur'aini; Nurlatifah (PT Inovasi Pratama Internasional, 2025)
This study aims to explore various innovations in Islamic Religious Education (IRE) learning methods that are relevant to the needs of students in the digital era. Using a library research approach, this study analyzes literature from multiple sources that discuss the development of integrative, contextual, and character- and technology-based learning methods. The findings reveal that innovations such as project-based learning, experiential learning, blended learning, and the integration of local culture make IRE more interactive, reflective, and meaningful. The study also emphasizes the crucial role of teachers as facilitators in creating a learning environment that supports students' spiritual, moral, and social development. These findings provide theoretical contributions to the development of IRE literature and practical insights for teachers, curriculum developers, and policymakers in designing more adaptive and transformative learning practices.